Assessment of the Factors Affecting the Intention to Invest in a P2P Lending Platform - Leckė, Gintarė; Milašiūtė, Gabrielė; Šeškevičiūtė, Akvilė (Socialiniai tyrimai, 2022)
The digitalisation of the financial system and the rapid growth of new financial technologies arecontributing not only to the change of the financial system, but also to the change of the way people makefinancial decisions. The development of financial technologies has led to the emergence of new financialservices and products, such as P2P lending. With the growth P2P lending market, the scientific literaturepays more and more attention to the analysis of investment intentions through P2P lending platforms and theassessment of the factors affecting the intention to invest (Dja’akum, 2019; Fiorentino et al., 2020; Khan etal., 2021Yang ir Lee, 2016; Poeteri, et al., 2021). It should be noted that, although the interest of researchersin this field is growing, the research in the European context is not sufficient, which reveals the relevance ofthis study. Thus, the aim of the present study is to assess the factors that affect the intention to invest throughP2P lending platforms in Lithuania.A theoretical review of the scientific literature revealed that previous empirical studies have categorised thefactors of the intention to invest through peer-to-peer lending platforms into individual and platform factors.Individual factors are understood as risk appetite, perceived risk, financial literacy, while platform factors areunderstood as perceived ease of use, perceived usefulness, trust. Attitude toward behaviour can be seen asboth an individual and a platform factor. Other factors, such as relative advantage, compatibility, complexity,perceived behaviour control are also distinguished in the scientific literature, but are not considered in theanalysis of the intention to invest through peer-to-peer lending platforms.Research data was collected through an online survey. The survey questionnaire was distributed onlinebetween February and April 2022. The survey sample consisted of 211 respondents. The conceptual researchmodel was developed using a Modified Technological Acceptance (TAM) model, which was performed usingthe Structural Equation Modelling (SEM) method.The SEM analysis revealed that the intention to invest through P2P lending platforms was indirectly influenced by the trust of the P2P lending platform, perceived risk and risk appetite factors. The indirect impactwas through attitude toward P2P lending platforms factor, which had a strong and significant positive impacton the intention to invest through P2P lending platforms. The effect of perceived usefulness and perceivedease of use on Lithuanian investors‘ attitudes towards P2P lending platforms was not statistically significant,and therefore no statistically significant effect of these factors on the intention to invest through P2P lendingplatforms was found.
Keywords: P2P lending; investment intention; TAM; SEM